The phenomenon of dynamic change of cardiac troponin levels in patients with spontaneous intracerebral hemorrhage increases in-hospital mortality independent of macrovascular coronary artery disease - Lesch, Hendrik; Kruska, Mathieu; Marx, Alexander; Haucke, Lea; Ebert, Anne; Becker, Louisa; Szabo, Kristina; Akın, Ibrahim; Alonso, Angelika; Fastner, Christian (Journal of the neurological sciences, 2025)
Background and aims - Growing evidence suggests worse outcomes in patients with spontaneous intracerebral hemorrhage (sICH) and elevated cardiac troponin (cTn) level. While the predictive value of isolated cTn elevation in sICH on outcomes is unclear, few studies have examined patients with follow-up measurement of cTn level. The aim of this study was to investigate the association of a dynamic change in high-sensitivity cTn I (hs-cTnI) levels with in-hospital outcomes in sICH patients. - Methods - This retrospective study included acute sICH patients between 2015 and 2021 with serial hs-cTnI level measurement. Group comparisons were performed between patients with dynamic hs-cTnI change, i.e., rise or fall of hs-cTnI levels on follow-up measurement >20 %, and those with stable hs-cTnI levels. Variables with suspected impact on in-hospital mortality were analyzed for their predictive value using multivariate logistic regression analysis. - Results - A total of 55/105 sICH patients were found to have a dynamic change in hs-cTnI levels. A dynamic change in hs-cTnI levels was significantly associated with in-hospital mortality. Frequency of intraventricular hemorrhage (IVH) was higher in the dynamic group, while vascular risk profile, burden of coronary artery disease and functional neurological status at admission were evenly distributed. While a dynamic change in hs-cTnI levels showed a trend, solely IVH independently predicted in-hospital mortality. - Conclusions - We suggest that a hs-cTnI dynamic is an expression of the acute myocardial ‘hit’ driven by sICH along the brain-heart axis leading to stroke-induced heart injury and not of ischemic myocardial infarction. IVH additionally contributes to the proposed pathomechanism of myocardial injury.
Online verfügbar: 23. Juli 2025, Artikelversion: 26. Juli 2025
Gesehen am 06.11.2025